Teacher Strategies in Teaching English at SMAS Muhammadiyah Kendari - Arista, Muslianti; Nasrullah, Rahmat; Faridawati (Mataoleo: Journal of English Education and Linguistics, 2025)
This study aimed at identifying the teacher strategies in teaching English. This study was descriptive qualitative research and conducted in SMAS Muhammadiyah of Kendari. The subject of this study was one English teacher. The researcher used convenience sampling in selected the subject. In collecting the data, classroom observation and interview were conducted. The observation was conducted in three times and the researcher used in-dept-interview to dig up information. The result showed that there were eight strategies, they are: recalling memory, brainstorming, Pair Work, students’ presentation, lecture method, multimedia method, independent study, & mastery learning.